2013
DOI: 10.1002/jez.1780
|View full text |Cite
|
Sign up to set email alerts
|

Swimming Capability and Swimming Behavior of Juvenile Acipenser schrenckii

Abstract: Acipenser schrenckii, the Amur Sturgeon, was a commercially valuable fish species inhabiting the Amur (Heilongjiang) River but populations have rapidly declined in recent years. Dams impede A. schrenckii spawning migration and wild populations were critically endangered. Building fishways helped maintain fish populations but data on swimming performance and behavior was crucial for fishway design. To obtain such data on A. schrenckii, a laboratory study of juvenile A. schrenckii (n = 18, body mass = 32.7 ± 1.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
34
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 26 publications
7
34
0
Order By: Relevance
“…It is reported that U crit (20°C) of Coreius guichenoti and Aristichthys nobilis (both Cyprinids) are 6.54 and 4.57 BL s −1 (20°C), respectively, after 2 d of starvation (Cai et al 2012. U crit of grass carp (8.94 BL s −1 ) was higher than either of these species.…”
Section: U Crit and Swimming Efficiencymentioning
confidence: 96%
See 2 more Smart Citations
“…It is reported that U crit (20°C) of Coreius guichenoti and Aristichthys nobilis (both Cyprinids) are 6.54 and 4.57 BL s −1 (20°C), respectively, after 2 d of starvation (Cai et al 2012. U crit of grass carp (8.94 BL s −1 ) was higher than either of these species.…”
Section: U Crit and Swimming Efficiencymentioning
confidence: 96%
“…1). Components of the respirometer included a motor, transducer, propeller, multi-aperture rectifier plate (Lucite) and a wire grid (Cai et al 2013). The transducer controls the voltage applied to the motor, allowing the propeller speed and flow velocity to be adjusted.…”
Section: Respirometermentioning
confidence: 99%
See 1 more Smart Citation
“…2014). To improve the effectiveness of fish passage for larger species, designs can be enhanced by incorporating orifices into the traditional pool and weir design, as reported in previous studies of the swimming performance of sturgeons (He et al 2013, Cai et al 2013. For example, the minimal slot width (in the vertical slot model) can be determined by the largest tail beat amplitude (TBA), and the slot velocities of upstream fishways should be lower than critical swimming speed (U crit ) of the fish in downstream fishways (Tu et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is easy to evaluate costs of activities such as migrating by measuring tail beat frequency (TBF) and observing body movements of the fish (Ohlberger et al 2007). Excess post-exercise oxygen consumption (EPOC) can be used to determine recovery time after fatigue, and resting pools should usually be required in fishways (Cai et al 2013). Other important design considerations include fish physiology, flow velocity and hydraulic conditions (Roscoe & Hinch 2010, Katopodis & Williams 2012.…”
Section: Introductionmentioning
confidence: 99%